Outcome analysis of early surgery and conservative treatment in neonates and infants with severe hydronephrosis - Qi-Fei Deng; Han Chu; Bo Peng; Xiang Liu; Yong-Sheng Cao (Journal of International Medical Research, 2021)
Objective The treatment strategy and timing of ureteropelvic junction obstruction (UPJO) in infants remain controversial. This study aimed to compare the effect of early surgical treatment (EST) and conservative treatment (CT) on neonates and infants with UPJO and their recovery of renal function and morphology. Methods Eighty neonates and infants with severe hydronephrosis were enrolled in this study. They received early pyeloureteroplasty or CT. Diethylenetriamine pentaacetate was used to assess renal function. Results There were no significant differences in renal function or renal indices at baseline between the two groups. At 3 and 6 months of follow-up, the anteroposterior diameter of the renal pelvis and the Society of Fetal Urology grade in the EST surgery group were significantly lower compared with those at baseline. The thickness of the renal cortex was greater in the EST group than in the CT group at 3 and 6 months of follow-up. After follow-up for 6 months, renal function in the EST group was significantly better than that in the CT group. Conclusion EST accelerates the recovery of renal morphological and functional indices in neonates and infants with severe hydronephrosis.